Peran UMKM dalam Mengatasi Masalah Kemiskinan di Provinsi Daerah Istimewa Yogyakarta - Ariyani, Diyah; Wulandari, Putri Wahyu (Journal of Economics and Business Research (JUEBIR), 2025)
This study analyzes the influence of tourism income, MSME growth, Human Development Index (HDI), and zakat on the poverty rate in the Special Region of Yogyakarta Province. Utilizing panel data from 5 regencies/cities during the period of 2018-2022, the study employs the panel data regression analysis method. The findings of the study indicate that tourism income and MSME growth have a negative but insignificant impact on poverty. This suggests that the benefits of these two sectors have not been evenly distributed to significantly reduce poverty. The HDI is found to have a negative and significant impact on poverty, emphasizing the importance of investing in human resource development as a long-term poverty alleviation strategy. Unexpectedly, zakat demonstrates a positive and significant impact on poverty, which could be attributed to inefficiencies in zakat management and distribution or other uncontrolled factors within the study. These findings highlight the need for a multi-dimensional approach to poverty alleviation, focusing not only on economic growth but also on enhancing human resource quality and improving income redistribution systems. The study provides crucial implications for policymakers in formulating more effective and integrated poverty alleviation strategies in the Special Region of Yogyakarta Province